PENGARUH KEBIJAKAN DIVIDEN, LEVERAGE KEUANGAN DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BEI - ARIEF WILIANTO (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
This research was conducted to know influence Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER), and Return On Equity (ROE) with stock price. Population used in this study were manufacturing companies went public, in which the research period in 2007-2010 and 130 samples obtained as a manufacturing company obtained by purposive sampling technique. Data taken from the Indonesian Capital Market Directory (ICMD) and financial statements. There are two variables that lifted the stock price as the dependent variable and the DPR, DER, and ROE as an independent variable. Data analysis technique used is multiple linear regression analysis. The results showed that DPR and DER has a significant influence on stock prices. And ROE do not have a significant effect on stock prices. In the partial testing, variables significantly influence DPR with a significance level of 0.000